MANAJEMEN PEMBERDAYAAN SUMBER DAYA MANUSIA DALAM PEMELIHARAAN DAN PASCA-PANEN TANAMAN KELOR PADA KELOMPOK USAHA MAJU BERSAMA DESA NOELBAKI - Benu, Yasper Anderias; Nendissa, Doppy Roy; Pudjiastuti, Sondang S.P. (Undana Press, 2023)
Moringa is a plant that has many benefits and is easy to develop because it can grow in a variety of land conditions, but in its development there are still many deficiencies where the development process is not accompanied by the application of management of human resources. The purpose of this study is to determine the implementation of management and empowerment strategies for human resources in the Maju Bersama Business Group in Noelbaki village. This study uses ordinal scale analysis, by analyzing the level of participation of members of the Maju Bersama Business Group through questionnaires and interviews and then assessed with scoring criteria. The results showed that in the joint-progress business group, the strategy of empowerment and management of human resources was not implemented properly, where the level of role of human resources in maintenance and post-harvest showed that 2 people were actively involved.